Pengaruh Lingkungan Kerja Dan Beban Kerja Terhadap Kepuasan Kerja Karyawan Wisma Sehati Cabang Bumi Serpong Damai (BSD) Tangerang Selatan - May Nena Ray Dalena (2021)
This research is a research using a quantitative approach which aims to find out and prove the effect of the work environment and workload on the job satisfaction of the employees of Wisma Sehati BSD Tangerang Selatan branch. The population in this research were 30 employees and the sample used in this research was the same number of 30 people using the saturated sample technique. In collecting data, the data was distributed using an online questionnaire via Google Form. The analytical tool used in this research is SmartPLS 3.3.3 with the analysis technique used is path analysis. The results obtained in this research are (1) the work environment has a significant and positive effect on job satisfaction and (2) workload has a significant and positive effect on job satisfaction.